Petrographic characterization of black shales from belata formation, peninsular Malaysia: Implication for fracability - Esther, O.B. (Offshore Technology Conference, 2020)
Successful fracturing processes in shale, during shale gas drilling and production, is an effective way to reduce environmentally and cost risks. Fracability of rocks is highly affected by the rockâs quartz, carbonate and/or clay content. Thus, a fair understanding of shale quartz, carbonate and/or clay content is critical in achieving an effective fracturing process. The objective of this paper is to qualitatively and semi-quantitatively characterise the quartz and clay minerals within the black shales of the Belata Formation. Twenty-two samples were analysed using Scanning electron microscopy (SEM) fitted with energy dispersive x-ray spectroscopy (EDS) and X-ray diffraction (XRD). The result showed slight variations in the concentrations of quartz, which are not too highly deviated from the recorded average. Chlorite and kaolinite are the dominant clay minerals within the black shales. However, the chlorite and kaolinite in Belata black shale show little effect on the fracability of the shales. The estimated brittle index indicated a high quartz/silica composition in the Belata black shales compared to clay minerals. The brittle index further suggested a high fracability with quartz concentration of about 86 . The range of fracability using the brittle index method is between 0.91 to 0.64, with an average of 0.79, which is considered very high. Thus, these shales could be fractured at various locations through hydraulic fracturing in order to improve their permeability for any flued within the shale. This finding provides new insight into the fracability of the Paleozoic shales in the Peninsular. Copyright 2020, Offshore Technology Conference